Discovery of quinuclidine modulators of cellular progranulin. (1st September 2021) - Lanter, James C.; Chen, Angela Y.-P.; Williamson, Toni; Koenig, Gerhard; Blain, Jean-François; Burnett, Duane A.
Graphical abstract: Phenotypic screening of an annotated small molecule library identified the quinuclidine tetrahydroisoquinoline solifenacin (1 ) as a robust enhancer of progranulin secretion with single digit micromolar potency in a murine microglial (BV-2) cell line. Subsequent SAR development led to the identification of 29 with a 38-fold decrease in muscarinic receptor antagonist activity and a 10-fold improvement in BV-2 potency. Abstract: Phenotypic screening of an annotated small molecule library identified the quinuclidine tetrahydroisoquinoline solifenacin (1 ) as a robust enhancer of progranulin secretion with single digit micromolar potency in a murine microglial (BV-2) cell line. Subsequent SAR development led to the identification of 29 with a 38-fold decrease in muscarinic receptor antagonist activity and a 10-fold improvement in BV-2 potency.